Determinants of Innovation - Bloch, Harry; Bhattacharya, M. (Kluwer Academic Publishers, 2004)
The study examines how firm size, market structure, profitability and growth influence innovative activity in small to medium sized Australian manufacturing businesses, using the recently released Confidentialised Unit Record File drawn from the Business Longitudinal Survey of the Australian Bureau of Statistics. Regression analysis is conducted to determine the factors that effect subsequent innovative activity for the full sample of businesses, as well as for sub-samples of firms from high and low-technological opportunity industries. Most variables, including size, R&D intensity, market structure and trade shares are found to be conducive to further innovative activity for the full sample and for high-tech firms. For low-tech industries, fewer variables are significant.